Finding a Common Voice: Lessons Learned from a Pilot Mental Health Literacy Intervention for Secondary Students with Disabilities. Issue 1 (1st January 2023) - Sinclair, James
ABSTRACT: The current study evaluates lessons learned from a feasibility and acceptability trial of the Think, Be, Do, curriculum (a mental health literacy curriculum) for transition age students (14–21) in special education classrooms. Six teachers and sixty-two students from a northwest state in suburban and rural settings participated in the intervention group and were exposed to the Think, Be, Do curriculum twice a week for five weeks. Data were collected from students, teachers, and observers. A mixed methods approach captured quantitative and qualitative data from participants. Results from the implementation suggest the curriculum was feasible to implement, acceptable to teachers for their classrooms, and had preliminary increases in student mental health literacy. Lessons learned from the initial implementation and implications for research and practice are discussed.